Peran Pemerintah Gampong Dalam Membangun dan Mengelola Dana Gampong Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Cut Megawati; Amzar Ardiyansyah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
This study aims at determining the role of country (Gampong) government in developing and managing Gampong bungets. The research method uses library research (secondary) and field research (primary) so it can be analyzed by using qualitative approach. From the results of the discussion, it can be concluded that the role of country government in building and managing country budgets is still far beyond expectations caused by internal disharmony and external ignorance so that the existing resources are not able to carry out the existing tasks. Thus, the country government should be more active in the management and development of country’s budgets by participating in seminars and lectures held by the local government.